Long Term Load Forecasting using Grey Wolf Optimizer - Artificial Neural Network - Yasin Z.M.; Salim N.A.; Ab Aziz N.F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power plant loads; Heuristic methods; Learning algorithms; Neural networks; Particle swarm optimization (PSO); Wind; Accurate prediction; Electrical load; Learning rates; Load forecasting; Long-term load forecasting; Mean absolute percentage error; Meta-heuristic techniques; Optimizers; Forecasting